PENERAPAN MODEL SIMAS ERIC UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI PEMANASAN GLOBAL DI KELAS XI MAN 1 PEKANBARU - Elvy Kartika Putri; Mitri Irianti; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to determine students cognitive study result by the application of Simas Eric model. This study was conducted in MAN 1 Pekanbaru. This study was a quasi experimental using intact group comparison design. The population in this study was student of XI MIA class in MAN 1 Pekanbaru. Sample on this study obtained from two classes of population based on homogeneity test and the sample was chooseen randomly so that experiment and control classed could be obtained. The data was collected by using cognitive study result test after Simas Eric model was applied in experiment class and conventional learning was applied in control class. The data was analize by using descriptive and inferential analysis. This study showed that the average number of students absorption ability which Simas Eric model was applied 80,61% and 72,44% for the conventional learning. It can be concluded that the application of Simas Eric model could enchace students’ cognitive study result on global warming material at XI class MAN 1 Pekanbaru.Keywords: Simas Eric model, cognitive study result, global warming